1899 Wyo. Rev. Stat. 1252, div. 5, tit. 1, ch. 3, § 5044 - (:unkn) unknown (General Publisher, 1899)
Whoever fights a duel, if death do not ensue, shall be fined one hundred dollars, and be imprisoned in the county jail not more than one year.
--
Keywords: DUELING